"Musical dish" efficiently induces osteogenic differentiation of mesenchymal stem cells through music derived microstretch with variable frequency. Issue 2 (25th January 2022) - He, Qiulin; Lin, Junxin; Zhou, Fanghao; Cai, Dandan; Yan, Yiyang; Shan, Yejie; Zhang, Shufang; Li, Tiefeng; Yao, Xudong; Ouyang, Hongwei
Abstract: Nonuniform microstretching (NUMS) naturally occurs in real bone tissues in vivo, but its profound effects have not been identified yet. In order to explore the biological effects of NUMS and static stretch (uniform stretch [US]) on cells, a new "musical dish" device was developed. Musical signal was used to provide NUMS to cells. More stress fibers, arranging along the long axis of cells, were formed throughout the cells under NUMS, compared with US and untreated control group, although cell morphology did not show any alteration. Whole transcriptome sequencing revealed enhanced osteogenic differentiation of cells after NUMS treatment. Cells in the NUMS group showed a higher expression of bone‐related genes, while genes related to stemness and other lineages were down‐regulated. Our results give insights into the biological effects of NUMS and US on stem cell osteogenic differentiation, suggesting beneficial effects of micromechanical stimulus for osteogenesis. The newly developed device provides a basis for the development of NUMS derived rehabilitation technology to promote bone healing.